Carbon-Fiber-Reinforced Polymer Intramedullary Nails Perform Poorly in Long-Bone Surgery - Fragomen, Austin T. (HSS J, 2018)
BACKGROUND: Carbon-fiber-reinforced (CFR) polymer has produced great excitement in the orthopedic community as a material that will reduce bone healing times and provide improved image quality. Osteotomy stabilized with an intramedullary (IM) nail has become a common technique to address post-traumatic malalignment of the lower extremity. PURPOSES/QUESTIONS: The following questions were asked: (1) Did CFR polymer nails provide a rapid healing time after long bone osteotomy, shortening, or fracture? (2) Did the CFR polymer nails produce unexpected complications? METHODS: A retrospective review was conducted in patients who received CFR polymer IM nails for various indications, from April 2016 to January 2017 in a deformity and trauma practice, ﻿using patient charts and radiographs. The primary outcomes were time to union and incidence of complications including nonunion, hardware failure, neurovascular injury, venous thromboembolism, and infection. RESULTS: Twelve patients who received CFR polymer IM nails in 16 limbs for various indications were included in our analysis. Patients were followed for an average of 16.9 months. Eleven limbs underwent realignment and were corrected an average of 23° through a diaphyseal osteotomy. Three limbs underwent limb-shortening surgery, an average of 25 mm, through an open, excisional osteotomy of the femoral diaphysis. Two diaphyseal, closed tibia fractures underwent routine IM nailing. The average time to union was 107.6 days, which included all limbs that united (11/16, 69%). Nonunion occurred in 5/16 (31%) of limbs. Complications recorded included nonunion and hardware failure, most of which resulted in unplanned surgery. CONCLUSIONS: The use of the CFR polymer IM nail was associated with loss of fixation and nonunion after surgeries that have traditionally healed uneventfully. The increased elasticity of the CFR polymer allows for more motion at the osteotomy/fracture interface than the stiffer titanium counterparts, exposing long-bone osteotomies to delayed union and nonunion, a finding seen with CFR polymer plates. The overwhelmingly poor early results of this device applied to a long-bone deformity practice have led these authors to abandon the use of this implant.